2021
DOI: 10.3390/buildings11060256
|View full text |Cite
|
Sign up to set email alerts
|

Coconut Fibre and Sawdust as Green Building Materials: A Laboratory Assessment on Physical and Mechanical Properties of Particleboards

Abstract: This paper evaluates, via a laboratory assessment, the physical properties (BS EN 323:1993, BS EN 324) and mechanical performance (BS EN 310: 1993) of hybrid particleboards using agricultural wastes, namely coconut fibre and sawdust. The process begins with the preparation of the materials where they are sieved and retained with the 5-mm sieve and then oven-dried. The hybrid particleboard mixed with the addition of resin (urea formaldehyde) was sprayed and hot pressed. The hot press temperature was set at 180 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…Building carbon neutrality is a major research focus in the field of architecture, with ongoing expansion and deepening of related research areas. The evolution of research hotspots in this field can be revealed through methods such as timeline spectra and keyword cluster analysis [41]. Timeline spectra can display the appearance and evolution of different clustering focuses, thereby helping researchers understand the development of various research fields.…”
Section: Emerging Research Frontiers and Hot Issues In Carbon-neutral...mentioning
confidence: 99%
“…Building carbon neutrality is a major research focus in the field of architecture, with ongoing expansion and deepening of related research areas. The evolution of research hotspots in this field can be revealed through methods such as timeline spectra and keyword cluster analysis [41]. Timeline spectra can display the appearance and evolution of different clustering focuses, thereby helping researchers understand the development of various research fields.…”
Section: Emerging Research Frontiers and Hot Issues In Carbon-neutral...mentioning
confidence: 99%
“…Ryłko-Polak et al [47] highlighted that lignin and its derivatives are also used in construction, mainly as additives in cement composites and bitumen substitutes [59]. Tawasil et al [60] studied the production of fiberboard made from waste coconut shells and found that the higher the composition of coconut fiber in the coconut fiber sawdust sheets was, the better the physical and mechanical performance became; the percentage of water absorption decreased, and the bending modulus of the plate also increased. Maximino et al [61] evaluated the applicability of sustainable building materials from waste with mycelium binders in the construction industry.…”
Section: Plant-based Resources For a Sustainable Construction Industrymentioning
confidence: 99%
“…Many studies on biocomposites have been conducted. For instance, natural fibre-based composites have been derived from rice straw, cogon grass, seaweed, and coconut (Jumaidin et al, 2020;Li et al, 2010;Motavalli et al, 2010;Tawasil et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, worldwide coconut production was approximately 61 million tons (Laura W., 2019). Besides being biodegradable and absent of health hazards, coconut shells have a high modulus and excellent lignin (more than 30%) (Ikumapayi et al, 2020;Tawasil et al, 2021). Several studies of the biocomposite from coconut shells have been carried out (Ismail et al, 2020;Ismail et al, 2022).…”
Section: Introductionmentioning
confidence: 99%